Current issues and development in hospitality and tourism satisfaction - Williams, J.; Uysal, Muzaffer (2013)
Stay ahead of your customers as their service expectations change!In Current Issues and Development in Hospitality and Tourism Satisfaction, experts from the field explore customer satisfaction strategies, examining both the long-term and short-term results. This vital tool shows you new and effective approaches for understanding customer satisfaction and providing quality service at all levels of the hospitality and tourism industry. Hospitality and tourism faculty and students as well as professionals will find this book useful for improving and providing quality service management.This book illustrates the complex relationship between customer and service provider, offering practical advice and techniques for maximizing consumer contentment. Current Issues and Development in Hospitality and Tourism Satisfaction contains models for meeting—and even surpassing—consumer expectations to increase the value of the customer’s experience. This essential resource includes various methods for managers to anticipate consumer needs and perceptions, reducing dissatisfaction.This book helps you: • incorporate existing and alternative measurements of satisfaction •measure and improve service quality • create and maintain social interaction linkages between staff and customer • identify the destination performance of your hotel and other destinations or attractions • evaluate consumer satisfaction with lodging services • increase cross-cultural service satisfaction •and much more!Tables and figures throughout the text help demonstrate the strategies, and bibliographies at the end of each chapter offer further reading. While there are other books that focus on customer satisfaction, Current Issues and Development in Hospitality and Tourism Satisfaction is rare in that it covers satisfaction issues as they apply to both hospitality and tourism.